MOTHERS' KNOWLEDGE AND PERCEPTION OF ADOLESCENT REPRODUCTIVE HEALTH BEHAVIOR: A LOCAL PERSPECTIVE ON ADOLESCENT FEMALES AGED 12-18 YEARS IN KEDIRI DISTRICT - Indah Jayani; Susmiati Susmiati; Eko Winarti; Devangga Darma Karingga; Sri Haryuni; Idola Perdana Sulistyoning Suharto (Universitas Kadiri, 2025)
The impact of negative reproductive health outcomes is greater for female adolescents than for males, so the role of parents in providing health education to female adolescents is an important thing that requires serious attention. Mothers are parents as primary caregivers who have an important role in the development of reproductive health in adolescents. Lack of knowledge and perception of mothers about reproductive health in parents can trigger reproductive health problems, such as unwanted pregnancies, abortions, early marriages, sexually transmitted diseases (STDs), and HIV/AIDS. The purpose of this study was to determine the relationship between knowledge and perception of mothers on adolescent reproductive health. The sample was adolescents aged 12-18 years in the working area of ​​the Ngasem Health Center, Kediri Regency, as many as 80 respondents who were obtained based on proportional random sampling techniques. The instrument used to measure the variables of knowledge, maternal perception and adolescent reproductive health used a questionnaire. Data analysis used the Spearman rank test with a significance level of 0.05. The results of the study showed that there was a relationship between maternal knowledge and adolescent reproductive health education with a fairly strong correlation value (r = 0.482), and there was a significant relationship between maternal knowledge and adolescent reproductive health education with a fairly strong correlation value (r = 0.482), there was also a significant relationship between maternal perception and reproductive health education in adolescents with a strong correlation value (r = 0.777). Efforts are needed to improve maternal knowledge and perception in order to provide reproductive education so that adolescents become more responsible for their reproductive health. Keywords: knowledge, perception, reproductive health, adolescent mother